Unified Policies, Healthier Journeys: Adressing the Used-Lead-Acid-Battery challenge in Bangladesh - Zaman, Atiq; Ahsan, Tahmina; Radia, N. Z.; Singha, K. K.; Hossain, M.; Hasan, K. (UNCTAD, 2024)
E-rickshaws play significant roles in Bangladesh’s society and economy, but there are major concerns about the health and environmental impacts related to the system in which they operate, in particular how their batteries are sourced and disposed of. This report reviews the current state of e-rickshaws and the recycling of Used-Lead Acid Batteries (ULABs) in Bangladesh, focusing on the regulatory landscape and policies ensuring sustainable practices, particularly in the context of e-mobility. Existing policies aim to address challenges associated with informal Used Lead-Acid Batteries (ULABs) recycling, environmental pollution, and public health hazards. However, notable policy gaps and challenges persist, hindering the effective implementation of sustainable practices.